Application of parallel computation to material models with a large numb r of internal variables - Feyel, Frederic; Cailletaud, Georges; Roux, Fran ois-Xavier (European Journal of Computational Mechanics, 1998)
The finite element code ZiBuLoN has been parallelized using the FEfl subdomain decomposition method for the use of non-linear mechanical behavior models which require a high number of internal variables. This paper describes the chosen paralle/ization technique, the polycrystalline model - a non-linear model requiring a large number of internal variables developed at the Centre des Materiaux de !’Ecole des Min es de Paris - and shows some tests which bear out the efficiency of the promoted methods for tlte computation of tridimensional complex structures involving a strong non-linear behavior.